2017
DOI: 10.17957/ijab/15.0435
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Pattern of Splice Variants of Amino Acid Transporter Genes from Rice Grown under Various Nitrogen Conditions and during Development

Abstract: Amino acid transporters (AATs) play indispensable roles in nutrient uptake and allocation for plants. Alternative splicing of gene's post transcription can increase diversity of protein and allow novel ways to regulate growth and development of plant. In this study, 11 OsAAT alternative-splicing genes with 24 kinds of predicted mRNAs were identified from 85 rice AAT genes; of these, 23 alternative-splicing open reading frames were actually expressed in rice. Quantitative real time-polymerase chain reaction res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Consistent with the results from genome-wide studies, the expression of abiotic stress-induced individual mRNA variants of several regulatory and structural genes is development- or tissue-specific [ 73 , 79 , 83 , 99 , 101 , 102 ], while the variants from other genes show differential expression in various tissues and/or at developmental stages [ 77 , 81 , 96 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. The spatial expression of splice variants has a potential significance for rice stress tolerance.…”
Section: Abiotic Stresssupporting
confidence: 70%
“…Consistent with the results from genome-wide studies, the expression of abiotic stress-induced individual mRNA variants of several regulatory and structural genes is development- or tissue-specific [ 73 , 79 , 83 , 99 , 101 , 102 ], while the variants from other genes show differential expression in various tissues and/or at developmental stages [ 77 , 81 , 96 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. The spatial expression of splice variants has a potential significance for rice stress tolerance.…”
Section: Abiotic Stresssupporting
confidence: 70%
“…Several recent studies have explored the interactions among AS, nitrate, and root development ( Fang et al 2017 ; Ishizawa et al 2019 ; Wang et al 2020 ). It has been reported that more than 1000 maize genes have exhibited specific AS modulations in response to N treatment, which altered early N responses ( Wang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more than 1000 maize genes have exhibited specific AS modulations in response to N treatment, which altered early N responses ( Wang et al 2020 ). AS variants of rice amino acid transporter genes ( OsAAT s) were regulated by natural variations in expression ratios in rice grown with various levels of nitrogen; these AS variants then regulated nutrient uptake and allocation ( Fang et al 2017 ). Root hairs play important roles in water absorption and nutrient uptake, and splicing factor 3b is involved in pre-mRNA splicing, which is associated with root hair development in response to light signals ( Ishizawa et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%